The effect of inter-implant distance on retention and resistance to dislodging forces for mandibular implant-tissue-supported overdentures. - Farhad Tabatabaian; Abolfazl Saboury; Zahra Sadat Sobhani; Vicki C Petropoulos (Tehran University of Medical Sciences, 2014)
The effect of inter-implant distance on retention and resistance of implant-tissue-supported overdentures is lacking in the literature. An in vitro study was performed to evaluate this effect for mandibular implant-tissue-supported overdentures retained by two ball attachments.An acrylic cast of an edentulous mandible was fabricated. Three pairs of implants were symmetrically placed at both sides of the midline. The inter-implant distance was 10, 25, and 35 millimeters in positions A, B and C, respectively. A framework simulating the overdenture was fabricated on the cast. Six attachment housings were placed within the overdenture. For each sample, two ball abutments were screwed onto the implant pairs and two pink nylon inserts were seated in their respective attachment housings. The samples were tested in three groups of 15 (A, B, and C). The testing machine applied tensile dislodging forces and peak loads were measured in three directions: vertical, oblique, and anterior-posterior. A one-way ANOVA followed by Tukey's HSD was used to determine groups that were significantly different. Tests were carried out at 0.05 level of significance.Peak loads for the anterior-posteriorly directed dislodging forces were significantly the highest for group C (P0.05).Inter-implant distance did not affect the vertical retention and oblique resistance of mandibular implant-tissue-supported overdentures; however, it affected anterior-posterior resistance.